The impact of sustainable tourism on quality of life among the marginalised community in Mabul Island, Sabah, Malaysia - Ismail, Illisriyani; Kumarusamy, Risidaxshinni; Kunasekaran, Puvaneswaran; Siow, May Ling; Ramachandran, Sridar; Khairuddin, Fatin Nornajla (Inderscience Publishers, 2021)
This study intends to reveal the level of quality of life among the local community of Mabul Island in coping with scarce resources due to tourism-related activities. This study examined the impact of sustainable tourism on the quality of life among the marginalised community in Mabul Island using a 2017 population census. Multiple regression analysis of survey data revealed that four factors significantly influence the local community's quality of life, namely social impact, economic impact, gender and tourism occupation. Results show that the social and economic impacts of sustainable tourism have significant positive influences on locals' quality of life, while environmental impacts do not affect the quality of life. Therefore, this study confirms the theory of social exchange demonstrating that the local community's involvement in the tourism industry results in more benefits than costs. Besides that, the study finds that economic impacts increase the quality of life of the local community; thus, tourism planners should provide entrepreneurial avenues to improve locals' business skills and change their quality of life for the better.